ASSESSMENT PRACTICES IN ENGLISH LANGUAGE TEACHING (A SYSTEMATIC LITERATURE REVIEW) - Rahmati; Nurul Kamaliah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2025)
This research is a Systematic Literature Review (SLR) that aims to map, analyze, and synthesize empirical findings regarding assessment practices in English Language Teaching (ELT). Through a systematic analysis of 29 relevant studies, this review reveals a significant gap between theoretical discourse and classroom implementation. On one hand, literature advocates for authentic and formative assessment; on the other, empirical evidence shows the enduring dominance of traditional and summative methods, particularly for assessing writing and grammar. Key findings identify Teacher Assessment Literacy as the primary determining factor, where teachers' practices are more often shaped by personal experience and intuition than by formal training. Furthermore, assessment effectiveness is highly dependent on the specific context, including curriculum policies and institutional culture. Based on this synthesis, the review concludes that enhancing assessment quality in ELT requires a systemic approach that prioritizes building teacher capacity through training focused on practical application (TALiP) and policies aligned with classroom realities.